Simulation of snowboarding on snow surface modelled with particle elements - Yoshida, T.; Hojo, A.; Kuratani, H. (Proceedings of the 6th International Conference on Sport Sciences Research and Technology Support - Volume 1: icSPORTS, 2018)
One approach for an efficient development of snowboards is quantification of prototype performance. A simulation model which represents the discrete behaviour of snow with particle elements is developed to evaluate snowboarding performance of prototypes. The particle behaviour is calculated using the discrete element method (DEM). A snowboard is considered to be a rigid body in the simulation. Four snowboards with different sidecuts are modelled to evaluate the influence on the turn. The simulation is able to confirm the difference of trajectory due to the sidecut radius. The smaller sidecut radius increases the attack angle of the board. As the result, lateral force acting on the board increases and the turn become sharply.